Design of an integrated radome-antenna system - Tan, Tony Tiong Hock (Nanyang Technological University, 2021)
The conventional radome was designed to shield and protect the antenna from the external environment and debris. A key operating principle of the radome is to ensure that it has no electromagnetic interferences and does not attenuate the electromagnetic waves transmitted and/or received by the antenna system. However, due to the physical boundary, out-of-band frequencies will be reflected, resulting in a high Radar-Cross- Section (RCS) of the object and radar signature. The Absorptive Frequency Selective Rasorber (AFSR) acting as a filter to the in-band frequency and as an absorber to out-of- band frequencies can be deployed or embedded into the radome array to allow transmission in the transmission band while performing RCS reduction on other frequencies. This niche capability greatly reduces the RCS signature of the object. An AFSR radome-antenna system comprises a wideband U-slot microstrip patch antenna integrated to a curved radome array, composed of 7x2 AFSR unit cells was proposed and realised in this thesis. The proposed microstrip patch antenna was able to operate at 10 GHz with a wide fractional bandwidth of 17.3%. The proposed AFSR unit cell has two channels namely: Transmission Channel and Absorptive Channel. The transmission channel comprises an air-filled Parallel-Plate-Waveguide that propagates the in-band incident wave. The absorptive channel leverage on the filtering capability from the bandstop frequency selective surface was designed to block the inband incident waves and allow out-of-band incident waves to pass through. These waves were absorbed by the commercial absorptive material to achieve the desired RCS reduction. The proposed AFSR obtained a good transmission band from 8.69 GHz to 11.47 GHz and accorded a fractional bandwidth of 27.8% at the operating frequency of 10.08 GHz. In addition, it exhibited a wide absorption band (absorptive rate > 80%) from 1.3 GHz to 8.7 GHz and 11.4 GHz to 15 GHz. As a whole, the proposed integrated curved AFSR radome-antenna system exhibited the transmission passband from 9.09 GHz to 11.02 GHz at the center frequency of 10.1 GHz, provided an improved antenna gain of 25%, and achieved more than 10 dB RCS reduction from 3 GHz to 15 GHz which clearly demonstrated the effectiveness and capability of the curved AFSR radome-antenna system.